Cisplatin and Cetuximab Treatment for Metastatic Cutaneous Squamous Cell Carcinoma: A Systematic Review. Issue 1 (January 2017) - Trodello, Cameron; Pepper, Jon-Paul; Wong, Michael; Wysong, Ashley
Abstract : BACKGROUND: Cutaneous squamous cell carcinoma (cSCC) is the second most common form of skin cancer and metastasizes in 2% to 5% of cases. OBJECTIVE: Systematic evaluation of published cases of metastatic cSCC (mSCC) treated with cisplatin or cetuximab from 1989 to 2014. MATERIALS AND METHODS: A literature search was performed to identify cases of mSCC treated with cisplatin or cetuximab. Patient demographics, tumor characteristics, response rates, and disease-free survivals were extracted. RESULTS: A total of 60 cases of mSCC treated with cisplatin and 9 cases treated with cetuximab reported in the literature from 1989 to 2014 were included in the analysis. Patients treated with cetuximab obtained a complete response of 67%, an overall response of 78%, and a median disease-free survival of 25 (range 3–48) months. Patients treated with cisplatin obtained a complete response of 22%, an overall response of 45%, and a median disease-free survival of 14.6 (range 3–112) months. CONCLUSION: Head-to-head prospective clinical studies between cetuximab and cisplatin are needed to determine which is more efficacious. In addition, prospective tumor registries and randomized controlled trials should be developed in order to establish the ideal systemic regimen in cSCC.